Answer:
Step-by-step explanation:
y - 2 = -2(x - 3)
y - 2 = -2x + 6
y = -2x + 8
Answer:
3
Step-by-step explanation:
3 is positive and -2.5 is negative 2 is greater than 2.50 so the answer is 3
Give me Brainllest
The answer is 1/4. Hope I could help! :D
Answer:
#1 is 3x + 4 =-17 #2 is 3x =-21 #3 is x = -7 #4 is 2x + x +4 = -17
Step-by-step explanation:
#1 gives you the problem ready to be worked out. #2 all you need to do to finish it is divide both sides by 3. #3 the answer is already there. #4 You need to combine the like terms then solve the problem.
Answer:
x + -2
Step-by-step explanation:
(editing answer to add how i got it)
3x +6=-3 (2x +4)
-3 (2x +4)
Multiply using the distributive property.
−
6
x
−
12 /2
3(2)(-3x - 4)
divide these by 2 will get you
SO ITS 3(2) +6 = 3(2) (2x +4)